2008
DOI: 10.1186/1471-2458-8-341
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary tuberculosis among people living with HIV/AIDS attending care and treatment in rural northern Tanzania

Abstract: Background: Tuberculosis is the commonest opportunistic infection and the number one cause of death in HIV/AIDS patients in developing countries. To address the extent of the tuberculosis HIV coinfection in rural Tanzania we conducted a cross sectional study including HIV/AIDS patients attending care and treatment clinic from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
44
5
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 14 publications
15
44
5
1
Order By: Relevance
“…Lower cumulative incidence might due to improved TB/HIV chronic care and introduction of new regimen which effectively prevent occurrence of TB among HIV. Overall cumulative density reported in this study was lower than studies done in many other Sub Sahara African countries including, Ethiopia with reported incidence rate ranging from 5.4 to 11 per 100 PY [25]- [28]. Lower incidence rate could be explained by improved TB/HIV Care and new introduction of regimen which effectively prevent occurrence of TB among HIV.…”
Section: Discussioncontrasting
confidence: 52%
“…Lower cumulative incidence might due to improved TB/HIV chronic care and introduction of new regimen which effectively prevent occurrence of TB among HIV. Overall cumulative density reported in this study was lower than studies done in many other Sub Sahara African countries including, Ethiopia with reported incidence rate ranging from 5.4 to 11 per 100 PY [25]- [28]. Lower incidence rate could be explained by improved TB/HIV Care and new introduction of regimen which effectively prevent occurrence of TB among HIV.…”
Section: Discussioncontrasting
confidence: 52%
“…This finding was in line with studies conducted in India (17%), Nigeria (16.8%, 14.4%, 9.6% [1][2][3][4]. However, relatively higher prevalence has been reported from Nepal (27.3%) and Nigeria (22.7%) [5,6], and lower results were reported from Northern Tanzania (8.3%) [7]. Slight variation on the magnitude of tuberculosis in HIV/AIDS patients may be due to differences of HIV infection rate in the population, TB-diagnostic facilities available, health care awareness of the community to seek health care for both TB and HIV.…”
Section: Discussionsupporting
confidence: 39%
“…For instance, an observational community-based ART cohort study conducted in South Africa to show shortterm and long-term risk of tuberculosis associated with CD4 cells recovery during antiretroviral therapy revealed that unadjusted TB incidence rates were 16.8, 9.3, 5.5, 4.6, 4.2 and 1.5 cases/100 person-years, respectively (P < 0.001) [14], during person-time accrued within CD4 cell strata 0-100, 101-200, 201-300, 301-400, 401-500 and more than 500 cells/μl. Similarly, low level of CD4 count was reported as risk factor for development of tuberculosis in HIV/AIDS patients from Tanzania [7] and Ethiopia [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…These results are almost equal to Bernard J Ngowi et al's fi ndings which shows the same prevalence as 45.0% and 30.0% in the age group of 25 to 34 years and 35 to 49 years respectively. 34 Yadav DK et al revealed that 60% of TB/HIV co-infected belonged to the age group (31-40) years, while 35.7% of subjects was belonged to age group (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years. 33 Mansoori D et al revealed that 64% of TB/ HIV infected patients were 20-40 years old and 36% were 41 years old or more.…”
mentioning
confidence: 99%